Conversations with ILRI scientists - Joerg Jores: Contagious bovine pleuropneumonia research - Jores, Joerg (International Livestock Research Institute, 2012)
In this episode, Joerg Jores, a molecular biologist at the International Livestock Research Institute (ILRI), talks about ILRI's ongoing research on contagious bovine pleuropneumonia, a livestock disease that is endemic in Africa, including recent findings about the pathogens that cause the disease.